The correlation between age and mandibular bone quality based on panoramic radiographs: Korelasi antara usia dan kualitas tulang mandibula berdasarkan radiografi panoramik - Irmayanti Meitrieka Amri; Ria N. Firman; Farina Pramanik (Makassar Dental Journal, 2021)
Introduction: As someone ages, the bone quality may change and may be seen on mandibular bone. The changes in mandibular bone quality may be assessed using a panoramic radiograph. The aim of this study was to describe mandibular bone quality and to know the correlation between age and mandibular bone quality on panoramic ra-diograph. Methods: Cross sectional correlation analysis; the population was panoramic radiograph archives of patients in Dental Radiology Installation RSGM Universitas Padjadjaran within the range of age 13-59 years old when the radiograph was taken so that obtained 48 samples. The mandibular bone quality was obtained with man-dibular alveolar bone resorption index (MM ratio) method using EzPax-Plus software. Results: The highest ave-rage number of MM ratio was 2.384 and the lowest was 2.2856. The results showed correlation coefficient bet-ween age and MM ratio on right mandible calculated with Spearman’s rank (rs) was -0.046 (p-value=0.757) and rs=-0.058 (p-value=0.697) between age and MM ratio on left mandible. Conclusion: There is no correlation bet-ween age and mandibular bone quality on panoramic radiographs in RSGM Unpad based on MM Ratio.